Planetary health indicators for the local level: opportunities and challenges in applying the happy planet index in Victoria, Australia. (September 2022) - Patrick, Rebecca; Henderson-Wilson, Claire; Lawson, Justin; Capetola, Teresa; Shaw, Amy; Davison, Mia; Freeman, Alison
The United Nations Sustainable Development Goals, New Urban Agenda and Paris Agreement on Climate Change are blueprints for health promotion action that mandate human health is linked inextricably to the health of the environment. In the Anthropocene, new indicators are required to promote community engagement with, and measurement of, healthy and sustainable wellbeing for people and planet. This study explored the need for a metric such as the Happy Planet Index that explicitly links human health to health of the environment for a local level scale in Australia. The project arose from an international coalition of health promoters advocating for 'planetary health' approaches. Qualitative description methods guided the study design involving key informant interviews ( n = 17) and four focus groups ( n = 27 participants) with health and/or sustainability academics, practitioners and policy-makers. Document analysis of health and environment indices and policy mandates augmented the analysis. Qualitative content analysis techniques were used to analyse the findings. There was strong interest for a local level composite indicator, such as a rescaled Happy Planet Index (life expectancy × life satisfaction × equity adjustment/ecological footprint) for use at a local level. The value of a composite index was: its ability to promote community engagement with planetary health thinking; an advocacy tool for joint health and sustainability policy; to justify programs on health and environmental co-benefits; and to provide a mechanism for correlative comparisons between local governments and national comparisons. However, disciplinary silos currently limit partnerships for health promotion and planetary health and a local composite index could help bridge these divides.